Representative fretting fatigue testing and prediction for splined couplings - Houghton, Dean (2009)
Spline couplings are a compact and efficient means for transferring torque between shafts in gas turbine aeroengines. With competition in the aerospace market and the need to reduce fuel burn from the flight carriers, there is an ever-present requirement for enhanced performance. Spline couplings are complex components that can fail from a variety of mechanisms, and are susceptible to fretting wear and fretting fatigue (FF). Due to the expensive nature of full-scale testing, this thesis investigates the use of the representative specimen (RS) concept for predicting fretting-induced damage between spline teeth.